2013 Delmar nurse's drug handbook : the information standard for prescription drugs and nursing considerations - Spratto, George R.; Woods, Adrienne (Clifton Park, New York : Delmar Cengage Learning, 2013)
Feel confident in your knowledge of over 770 FDA-approved drugs with this handbook as your trustworthy and accurate drug information resource. This vital resource clearly describes the uses, side effects, contraindications, actions, and dosages for each drug covered. Each entry also provides information for effective drug administration and improved patient communication.
Chapter 1: A-Z listing of drugs -- Chapter 2 -- Appendix 1: Commonly used abbreviations and symbols -- Appendix 2: Medication errors: the importance of reporting -- Appendix 3: Controlled substances in the United States and Canada -- Appendix 4: Pregnancy categories: FDA assigned -- Appendix 5: Calculating body surface area and body mass index -- Appendix 6: Elements of a prescription -- Appendix 7: Easy formulas for IV rate calculation -- Appendix 8: List of combination drugs -- Appendix 9: Drug/food interactions -- Appendix 10: Drugs whose effects are modified by grapefruit juice -- Appendix 11: Drugs that should not be crushed -- Appendix 12: National patient safety goals (NPSG) -- Appendix 13: Cultural aspects of medicine theraphy -- Appendix 14: Common Spanish phrases and terms used in a health care setting -- Appendix 15: Medication reconciliation/overdose/misuse.
Includes index.
Keywords: DRUGS HANDBOOKS, MANUALS, ETC